Microwave sintering of zirconia-toughened alumina (ZTA)-TiO2-Cr2O3 ceramic composite: The effects on microstructure and properties - Manshor H.; Abdullah E.C.; Azhar A.Z.A.; Sing Y.W.; Ahmad Z.A. (Elsevier Ltd, 2023)
Alumina; Ceramic materials; Densification; Density (specific gravity); Fracture; Fracture toughness; Grain growth; Mechanical properties; Microstructure; Microwave heating; Microwaves; Sintered alumina; Titanium dioxide; Vickers hardness; Zirconia; Conventional heating methods; Homogeneous microstructure; Lower sintering temperatures; Microstructural analysis; Microstructure and properties; Microwave sintering; Microwave sintering methods; Zirconia toughened alumina; Sintering